2013
DOI: 10.1016/j.celrep.2013.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Cooperation of Immune Master Regulators IRF3 and NFκB in RNA Pol II Recruitment and Pause Release in Human Innate Antiviral Transcription

Abstract: Transcription factors IRF3 and NFκB, are activated by external stimuli, including virus infection, to translocate to the nucleus and bind genomic targets important for immunity and inflammation. To investigate RNA polymerase II (Pol II) recruitment and elongation in the human antiviral gene regulatory network, a comprehensive genome-wide analysis was conducted during the initial phase of virus infection. Results reveal extensive integration of IRF3 and NFκB, with Pol II and associated machinery, and implicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 65 publications
7
64
1
2
Order By: Relevance
“…18,19,31,32,43 Conversely, RelA, as well as other NF- κ B subunits, can modulate the DNA binding properties of other transcription factors. 42,43 Thus, in addition to their well-studied direct DNA binding properties, each of these transcription factors appears to function in the nucleus as a signaling cofactor that influences the DNA binding and transcriptional potential of their binding partners even at locations within the genome where no consensus DNA binding site for the cofactor is present.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,31,32,43 Conversely, RelA, as well as other NF- κ B subunits, can modulate the DNA binding properties of other transcription factors. 42,43 Thus, in addition to their well-studied direct DNA binding properties, each of these transcription factors appears to function in the nucleus as a signaling cofactor that influences the DNA binding and transcriptional potential of their binding partners even at locations within the genome where no consensus DNA binding site for the cofactor is present.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, and given the fact that many developmental and immune genes are regulated by transcriptional pausing (4,6,8,14,23,24), we hypothesized that Nup98 also may regulate virus-induced antiviral genes. We found that Nup98 plays a broadly antiviral role in insects; cells or adult flies depleted of Nup98 are more susceptible to infection against a panel of disparate RNA viruses.…”
Section: Significancementioning
confidence: 99%
“…We propose that the cGAS/STING/TBK1 cascade is an important contributor to basal maintenance of a primed state for ISGs. Interferon sensitization has been hypothesized to contribute to maintenance of a basal state priming for responsive cell lines that facilitates rapid induction of target genes (46)(47)(48). Changes in basal priming of ISGs may contribute to alterations in the antiviral response phenotype and provide an avenue for modifying the antiviral response in a cell-specific manner.…”
Section: Figmentioning
confidence: 99%